Single-item dynamic lot-sizing problems: An updated survey - Brahimi, Nadjib; Absi, Nabil; Dauzère-Pérès, Stéphane; Nordli, Atle (European journal of operational research, 2017)
•Almost 300 papers on the single item lot sizing problem are surveyed.•A structured classification is presented for solution approaches and different extensions of the single item lot sizing problem.•Future research directions are proposed. Following our previous paper (Brahimi, Dauzère-Pérès, Najid, & Nordli, 2006), we present an updated and extended survey of Single-Item Lot-Sizing Problems with focus on publications from 2004 to 2016. Exact and heuristic solution procedures are surveyed. A concise and comprehensive summary of different extensions of the problem is given. The classification of the extensions is based on different characteristics such as resource limitations, assumptions on demand and cost structure. The large number of surveyed papers shows the increased interest of researchers in lot-sizing problems in general and in single-item problems in particular. The survey and the proposed classification should help researchers to identify new research topics, to propose relevant problems and/or novel solution approaches.